Le pluralisme culturel: peuples et cultures - Martin, Jean Marie (Schola Salernitana - Annali, 2017)
The kingdom of Sicily sheltered different «peoples»: «Romans», Lombards, Greeks, Saracens, Jews. Each one was distinguished by its personal law, its language, its religion (or rite). Some Greeks and Arabs belonged to the king’s entourage. In Monte Cassino at the end of the 11th century, then in the palace of Palermo in the 12th century, philosophical and scientific Greek and Arabic texts were translated into Latin. Among the Christians, the Roman and Byzantine rites were admitted; but during the 13th century many Greeks lost their own culture.